Galectin-1 as a predictive biomarker in ovarian cancer - Mahak Masoodi; Zafar A. Shah; Afaq H. Beigh; Sheikh Zahoor Ahmad; Abdul Wahid Mir; Besina Yasin; Roohi Rasool; Khalid Z. Masoodi; Gull Mohammad Bhat (BMC, 2021)
Abstract Aim There is an urgent need to set up a useful biomarker for ovarian cancer. Galectin-1 is a promising carbohydrate-binding protein which plays a remarkable role in various malignancies yet its clinical significance is questionable. In this study, we have tested the clinical implications of serum Galectin-1 levels in patients with ovarian tumours. Main methods Serum Galectin-1 levels were quantified in 84 newly diagnosed ovarian tumour patients and 20 healthy controls by Enzyme Linked Immuno Sorbent Assay during the course of the disease. Therefore the samples were taken at diagnosis, after surgery and after chemotherapy. Key findings The Galectin-1 levels were found to be associated with various variables of Ovarian Cancer patients. The levels were found to be prominently high in postmenopausal patients. Galectin-1 levels were raised in epithelial ovarian tumours with significantly high levels in serous subtype. A decrease in Galectin-1 levels post-surgical intervention and after receiving chemotherapy was found. Galectin-1 levels evidently distinguished between normal, benign, malignant and metastatic cases as compared to CA125 levels. Galectin-1 demonstrated to be a better biomarker than CA125 according to the Receiver Operating Characteristic (ROC) curve analysis. Significance The study emphasizes that serum Galectin-1 may serve as a better surrogate biomarker in Ovarian Cancer for early detection, discriminating between malignant and benign abdominal masses and monitoring the progression of the disease and response to treatment.